Book Review: A review of “Cultural landscapes” - Yacher, Leon (The Professional Geographer, 2010)
Keywords: book.review; dept.egm

Photojournal: distant beats: tradition and change in senegal - Yacher, Leon (Focus on Geography, 2010)
Keywords: Senegal; cultural change; cultural geography; cultural influence; cultural landscape; cultural tradition; dept.egm; music

Sabbatical leave report: sabbatical Spring 2010 - Yacher, Leon I. (2010)
The purpose of the project was to travel to Paraguay to explore the history of geography as a science in that country, including identifying the foremost geographers who helped introduce and establish geography as a science in that country. No such study on the history of geography in Paraguay had been previously undertaken anywhere. Further research will be needed, but the collected material is ample for at least two article-length publications.
Keywords: dept.egm; faculty_collection

History of Geography as a Science in the Republic of Paraguay. - Yacher, Leon I. (2010)
Keywords: dept.egm; faculty_collection; sabbatical_report

Jaltomata parviflora (Solanaceae) una nueva especie del Norte del Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2010)
Keywords: dept.egm; ⛔ No DOI found